2017
DOI: 10.1021/acs.energyfuels.7b01639
|View full text |Cite
|
Sign up to set email alerts
|

Partially Oxidized Asphaltene as a Bitumen Viscosity Reducer

Abstract: Heavy oil/bitumen with asphaltene requires high energy consumption for transportation, because of its high viscosity. This often causes serious pipeline problems; therefore, it is necessary to reduce the viscosity to resolve these issues. In this paper, we propose a new simple method to reduce the viscosity of diluted bitumen using partially oxidized asphaltene without removing asphaltene. This partially oxidized asphaltene, modified by exposing asphaltene to ozone, has a strong affinity to nonoxidized asphalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous reports of oxidizing asphaltene to facilitate its separation from crude oil 14 or to reduce bitumen viscosity 16 have shown that treatment with potassium permanganate 14 or ozone 16 resulted in increased hydrophilicity, which ultimately facilitated precipitation from oil. We hypothesized that such oxidized derivatives of asphaltene, termed asphaltene oxide (AO), may function as economically viable catalysts due to the low cost of the precursor while providing insights into the intrinsic chemistry displayed by GO and other carbocatalysts 17 .…”
mentioning
confidence: 99%
“…Previous reports of oxidizing asphaltene to facilitate its separation from crude oil 14 or to reduce bitumen viscosity 16 have shown that treatment with potassium permanganate 14 or ozone 16 resulted in increased hydrophilicity, which ultimately facilitated precipitation from oil. We hypothesized that such oxidized derivatives of asphaltene, termed asphaltene oxide (AO), may function as economically viable catalysts due to the low cost of the precursor while providing insights into the intrinsic chemistry displayed by GO and other carbocatalysts 17 .…”
mentioning
confidence: 99%
“…In fact, both differences and relationships exist between the viscosity and the pour point in terms of certain physical properties that affect the viscosity of heavy oil. Thus, asphaltene should be considered the main factors affecting viscosity reduction, but the effects of resin and paraffin and the self-aggregation behavior of the highly viscous contents of crude oil should not be ignored …”
Section: Background Of Molecular Simulationmentioning
confidence: 99%
“…Thus, asphaltene should be considered the main factors affecting viscosity reduction, but the effects of resin and paraffin and the self-aggregation behavior of the highly viscous contents of crude oil should not be ignored. 17 Asphaltene consists of alkyl branches made up of C, H, and O and the functional groups of heterocyclic polycyclic and aromatic hydrocarbons or naphthene. The molecules of asphaltene interact with each other to form hydrogen bonds as an interlocking network of complex structures.…”
Section: Background Of Molecular Simulationmentioning
confidence: 99%
“…However, due to the complex stratum, low stratum temperature, high content of crude oil gel, and asphaltene, the stranded crude oil has high viscosity, which brings great challenges to its exploitation and transportation [ 3 , 4 , 5 ]. Therefore, reducing the viscosity of heavy oil and improving its fluidity are urgent problems to be solved [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%